The Role of Stem Cell Therapeutics in Wound Healing: Current Understanding and Future Directions. (September 2016) - Sorice, Sarah; Rustad, Kristine C.; Li, Alexander Y; Gurtner, Geoffrey C.
Abstract : Background: Chronic wounds present unique challenges for healthcare providers as they place patients at increased risk for various morbidities and mortality. Advances in wound care technology have expanded the treatment options available for wound management, but few products fully address the underlying core deficiencies responsible for the development of poorly healing wounds. In the future, addressing these derangements will undoubtedly play a key role in the treatment of these patients. Broad enthusiasm has surrounded the field of stem cell biology, which has shown great promise in repairing damaged tissues across numerous disease phenotypes. Methods: In this review, we provide a comprehensive review of the literature and evaluate the present landscape of wound therapeutics while discussing the rationales and allure behind stem cell–based products. We further propose 2 challenges that remain as new stem cell–based therapies are being developed and as this technology moves toward clinical translation. Results: Given the relatively young age of this newer technology in wound healing, numerous challenges continue to surround its effective use including identifying the ideal population of stem cells to use and determining the optimal cell delivery method. However, significant forward progress has been made, with several clinical trials beginning to demonstrate reliable clinical benefit. Conclusion: The upward trajectory of stem cell technologies provides an exciting opportunity to positively impact patient outcomes through the controlled application of regenerative cell–based therapy.